(untitled) (Patrimônio e Memória, 2006)
This paper discusses the public policies and their basis concerning the environment and, its relation to the communities that live in these areas. It supposes the environmental preservation leads to the consolidation of a protected area in its natural dynamics. From this conception these policies must avoid that external factors to the processes belonging to the environment act to alter its social and natural characteristics. These are controversial questions put in evidence through this reflection.